STUDI PERBANDINGAN FAKTOR REDUKSI (f) DARI TAHANAN GLOBAL DENGAN FAKTOR REDUKSI PARSIAL MATERIAL PADA KASUS BETON BERTULANG DENGAN METODE LRFD - Harmayani, Kadek Diana (Jurnal Ilmiah Teknik Sipil; Vol. 9, No. 1 Januari 2005)
A reinforced concrete structure can guarantee its safety by giving strength capacity or design strength more than any combination of working load effect. Design strength can be obtained by multiplying normal strength with reduction value of f strength less than one and nominal load is multiplied with the load factor with the value more than one. It can be written as factored resistance ³ effect of factored loads. Resistance factor can be expressed in some ways. Such as ACI Building Code was expressed as fRn ³ D Dn + L Ln, where f was resistance factor and D, and L were load factor for dead load and live load. Meanwhile CEB explained about resistance factors with reduction factor directly to its material, fc`/c and fy/s where c and s were partial material of safety factor or under strength material factors for concrete and steel. Herewith result from concrete material variability, the variety coefficient compression strength of concrete ( Wfc) had great influence to the reduction factor both global reduction factor from ACI and material partial reduction factor from CEB. The increase of load ratio (L/D) would add space between factor of dead load (D) and live load (L) were wider. With the increase of the value index gave the increase of safety condition. The result of the study was obtained that the influence of small dimension was to the global reduction factor and material partial reduction factor. After comparing the results obtained from the calculation method using global reduction factor (ACI) with material partial reduction factor (CEB), it could be drawn a conclusion that for beam and coloum using global reduction factor, its capacity to hold dead load was more than 13 % than material partial reduction factor.
Keywords: reduction factor, global resistance, partial material, reinforced concrete, LRFD method